Pro‐inflammatory cytokines/chemokines, TNF‐α, IL‐6 and MCP‐1, as biomarkers for the nephro‐ and pneumoprotective effect of silibinin after hepatic ischemia/reperfusion: Confirmation by immunohistochemistry and qRT‐PCR. Issue 4 (26th January 2022) - Kyriakopoulos, Georgios; Lambropoulou, Maria; Valsami, Georgia; Kostomitsopoulos, Nikolaos; Konstandi, Ourania; Anagnostopoulos, Konstantinos; Tsalikidis, Christos; Oikonomou, Panagoula; Simopoulos, Konstantinos; Tsaroucha, Alexandra K.
Abstract: The present study investigated the potential nephro‐ and pneumoprotective effect of silibinin (Si) after hepatic ischemia–reperfusion (I/R) injury, by measuring pro‐inflammatory factors. Sixty‐three rats were randomly assigned into three groups, as follows: (a) the sham group ( n  = 7 rats), subjected to opening and closing the abdomen; (b) the control group ( n  = 28 rats), subjected to 45‐min hepatic ischemia followed by reperfusion; and (c) the silibinin group ( n  = 28), subjected to 45‐min hepatic ischemia followed by intravenous administration of lyophilised SLB‐HP‐β‐CD before reperfusion. Control and silibinin groups were further subdivided into time‐point groups, according to the duration of reperfusion. TNF‐α, IL‐6 and MCP‐1 expressions were determined immunohistochemically and by qrT‐PCR at each time‐point. Kidney TNF‐α expression was significantly lower at 180 and 240 min, while lung TNF‐α expression was significantly lower at 240 min. Comparison between the control and Si group at the same time‐points showed very strong evidence of difference at 240 min, with the levels of IL‐6 shifting towards lower values in the Si group. Finally, we found a high MCP‐1 expression after 120 min. We conclude that hepatic I/R injury remotely increases pro‐inflammatory mediators in the kidney and lung, whereas silibinin shows a time‐dependent nephro‐ and pneumoprotective effect.